The dynamics between state control and metropolitan governance capacity - Helena Tolkki; Arto Haveri (Administrative Sciences, 2020)
Due to the national importance of metropolitan areas, central governments seek to make them as attractive and competitive as possible. In many cases, this is done through state control over metropolitan areas and their governance arrangements. This article examines the relationship between state control and metropolitan governance capacity based on a comparative case study of four metropolitan areas: Auckland, Dublin, Montreal and Oslo. These areas represent different models of metropolitan governance, as well as different forms of state control. We studied state control by focusing on political and administrative decentralization: how independently can the metropolitan government make decisions and perform its tasks? The conclusion is that the different dimensions of decentralization are connected to capacity, but not straightforwardly. This study indicates that state involvement through different forms of control can increase metropolitan governance capacity, but only if it is combined with mandate and supportive policy actions.
Keywords: 350; capacity; control; decentralization; governance structures; metropolitan governance